Molecular Docking of Shallot (Allium ascalonicum) Active Compounds to Lanosterol Enzym 14-Alpha Demethylase and Squalene Monooxygenase for Antifungi Potential Activity - Eka sukmawaty; Nur Alfisah; Masriany Masriany; Hafsan Hafsan (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2022)
Shallots (Allium ascalonicum) are one of the important horticultural export commodities in Indonesia, but the productivity of shallots has decreased due to the attack of pathogenic fungi. This study was aimed to determine the potential of active shallot compounds as ligands for inhibiting the activity of the enzyme lanosterol 14-alpha demethylase (ID: 4LXJ) and squalene monooxygenase (ID: 6C6R) enzymes which play an important role in the biosynthesis of ergosterol or fungal cell membranes. The molecular docking used the Autodock Vina (PyRx) program, an analysis of molecule interaction used PyMol, and Discovery Studio 2019 to analyze the types of bonds between molecules. Thirty-nine ligands from shallot compounds are docked to the anti-fungal target protein. The results showed ascalonicoside A1, ascalonicoside A2, ascalonicoside B, quercetin, isorhamnetin, quercetin di glucoside, quercetin tri glucoside, ethyl palmitate and benzyl salicylate have the potential to be anti-fungal to the enzyme lanosterol 14-alpha demethylase and squalene monooxygenase enzyme that responds to the synthesis of fungi cell wall. These ligand compounds bind to the target protein's amino acid residues with hydrogen and hydrophobic bonds. This research showed that shallot was the potential to be replicated as an anti-fungus for many purposes.